Strategy For Handling Fishermen's Slums in Galesong, Takalar Regency Based on Community Participation - Dzulqarnain Aras (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2022)
Slums as urban phenomenon is one of the problems faced in urban development Metropolitan MAMMINASATA reconditioned the process of urban development indirectly in the dynamics of developing slum areas in the District Galesong. This research aimed to investigate the typology of the development of slums and the sustainable handling strategy of the settlement. The research approach of the quantitative research used the descriptive and quantitative method and SWOT analysis. The research results indicted that the typology of the slums settlement inÂ  Galesong sub-district was the heavy typologi of the slums settlement, which was dominated by poor community and the minimum availability of the adequate infrastructure. Consequently, the community-participation-based handling strategy was needed to handle the slums settlement through theÂ  empowerment the participation in increasing the quality of slums settlement.